The power of problem based learning : a practical "How To" for teaching undergraduate courses in any discipline - Duch, Barbara J.; Groh, Susan E.; Allen, Deborah E. (Virginia : Stylus., 2001)
Problem-based learning (PBL) is a powerful teaching methodology which uses real-world problems to promote life-long habits of learning. This text presents the University of Delaware's knowledge and experiences of PBL.
includes index.
Keywords: Problem-based learning -- Handbooks, manuals, etc; Postsecondary education -- Handbooks, manuals, etc; Postsecondary education